2022
DOI: 10.4103/njms.njms_378_21
|View full text |Cite
|
Sign up to set email alerts
|

Midface fracture pattern in a tertiary care hospital – A prospective study

Abstract: Introduction The midface with multiple bones and cavities is vulnerable to fractures more commonly. Midface is one of the most frequently injured areas of the body, accounting for 23%–97% of all facial fractures. The classic LeFort type of fractures are uncommon nowadays and a more common picture is more severe forms primarily due to the high-speed vehicles that are a major cause of these fractures. It, therefore, has become imperative to determine the commonly occurring patterns of fractures in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
2
0
0
Order By: Relevance
“…The incidence of MFT and related fractures has been reported more frequently in the 20-29 age group by some authors [14][15][16][17][18][19][20][21] or in the 30-39 age group by others [22][23][24]. In our study, the mean age of the patients who underwent extraction due to maxillofacial injury was 29.75 ± 19.46 years, which was consistent with the mean age values reported in the literature.…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of MFT and related fractures has been reported more frequently in the 20-29 age group by some authors [14][15][16][17][18][19][20][21] or in the 30-39 age group by others [22][23][24]. In our study, the mean age of the patients who underwent extraction due to maxillofacial injury was 29.75 ± 19.46 years, which was consistent with the mean age values reported in the literature.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies in the literature show a different predominance in the etiology of facial fractures: an Indian study conducted in 2019 on 944 patients with facial trauma, with 19% midface fractures, found that the leading cause was by far road traffic accidents [ 17 ]. The same predominance of road traffic accidents is mentioned in another study from Saudi Arabia (2019) [ 18 ] and India (2022) [ 19 ].…”
Section: Discussionsupporting
confidence: 71%